Design and Planned Obsolescence. Theories and Approaches for Designing Enabling Technologies. (28th July 2017) - Zallio, Matteo; Berry, Damon
Abstract: We are currently living in a decade where smart objects and Internet of Things (IoT)-based devices are becoming part of daily life in different contexts. This research seeks to investigate and verify, by using a formal literature review methodology, the most visible aspects of technological development, within the Industry 4.0 and IoT scenario, in relation to the theories of the so called " Planned Obsolescence ". This study covers a defined number of works on Design theories and practices on how to face the issue of built-in obsolescence of devices in the era of the Connected Devices. The majority of the works studied are useful to create substrates of essential knowledge that strengthen the concept of premature ageing of technological devices and it has been noticed that the discipline of Design can be used as an incentive to extend life, improve the usability of existing products and empower user abilities.